2016
DOI: 10.1039/c6cp01940d
|View full text |Cite
|
Sign up to set email alerts
|

The role of the environment in the ion induced fragmentation of uracil

Abstract: The fragmentation of uracil molecules and pure and nano-hydrated uracil clusters by (12)C(4+) ion impact is investigated. This work focuses on the fragmentation behavior of complex systems and the effect of the environment. On the one hand, it is found that the environment in the form of surrounding uracil or water molecules has a significant influence on the fragmentation dynamics, providing an overall 'protective' effect, while on the other hand we observe the opening of specific fragmentation channels. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 76 publications
3
37
1
Order By: Relevance
“…However, independent of the neutral precursor-cluster size, the energy necessary to break those intramolecular bonds is considerably higher than the strength of intermolecular bonds within the cluster. A similar observation (formation of molecular fragments attached to intact clusters) were recently made by Avaldi and co-workers [10]. They described this phenomenon as a nonstatistical process associated with a localized energy deposition followed by ultrafast dissociation before energy redistribution.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…However, independent of the neutral precursor-cluster size, the energy necessary to break those intramolecular bonds is considerably higher than the strength of intermolecular bonds within the cluster. A similar observation (formation of molecular fragments attached to intact clusters) were recently made by Avaldi and co-workers [10]. They described this phenomenon as a nonstatistical process associated with a localized energy deposition followed by ultrafast dissociation before energy redistribution.…”
Section: Resultssupporting
confidence: 76%
“…Avaldi and Huber [10] investigated the fragmentation of isolated uracil molecules as well as non-hydrated and hydrated uracil clusters induced by collisions with 12 C 4+ cations. They showed that overall the surrounding water has a protecting effect, reducing the damage and the yield of low mass fragments by one to two orders of magnitude for non-hydrated and hydrated uracil clusters, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, Barc et al [25] showede xperimentally that the reactivity of uracil was inhibited in presence of water and supposed that uracil was stabilised by the hydrogenb ond network developed with water,t hey also showed that the presenceo fw ater enhances the dissociation corresponding to the production of C 3 H 3 NO + (69 Da), while partially inhibiting other channels. Markush et al [26] reported the same effect in their experimental work on hydratedu racil using 12 C 4 + ion impacts. They also observed hydrated fragments indicating the strong interaction between uracil and water molecules.I na ccordance with these results, the experimentalw ork of Castrovillia nd co-workers [27] reported the stabilisinge ffectp layed by water when studying clusters of hydrated 5Br-uracil.…”
Section: Introductionmentioning
confidence: 66%
“…showed experimentally that the reactivity of uracil was inhibited in presence of water and supposed that uracil was stabilised by the hydrogen bond network developed with water, they also showed that the presence of water enhances the dissociation corresponding to the production of C 3 H 3 NO + (69 Da), while partially inhibiting other channels. Markush et al . reported the same effect in their experimental work on hydrated uracil using 12 C 4+ ion impacts.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many gas phase studies of nucleobases, and to a lesser extent nucleosides, irradiated with ionising electromagnetic radiation, electrons, and heavy particles [1] [16]. Investigation of larger components of DNA are challenging due to the difficulty in vaporizing these large molecules, but a few experiments have been undertaken or are in development [17] [18] [19] [20].…”
Section: Introductionmentioning
confidence: 99%